Fixel based analysis on diffusion MRI of COVID-19 survivors - Sapna S Mishra; Tapan Kumar Gandhi; Bharat Biswal (NeuroImage: Reports)
The underlying mechanisms of long-term sequelae of the COVID-19 infection, including fatigue, memory issues, and attention deficit, remain to be understood. Therefore, we investigated the Diffusion MRI scans of 73 COVID-Recovered Patients (CRPs) and 46 Healthy Controls (HCs) using Fixel-based analysis to study the sub-voxel microstructural properties of nervous tissue. We compared the Fiber Density (FD), log scaled Fiber Cross-section (log-FC), and a combined fiber density and cross-section measure (FDC) across the cohorts. Our study reveals significant alterations (pFWE <0.01) in the uncinate fasciculus (FD, log-FC, FDC; CRP > HC), perigenual corpus callosum (FD; CRP > HC), fornix (log-FC, FDC; CRP > HC), right arcuate fasciculus (FD; CRP < HC), as well as bilateral clusters in the inferior longitudinal fasciculus (FD; CRP < HC), and the corticospinal tract (FD; CRP < HC). We suggest that these changes may be related to microscopic changes in axonal volume. Notably, the tracts identified in this study highlight the involvement of the limbic system and the visuospatial attention network in the disorder. We expect our findings to improve our understanding of the neurological underpinnings of COVID-19.